2006
DOI: 10.1007/s00428-006-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinomas of the lung—are these histogenetically heterogeneous tumors?

Abstract: Sarcomatoid carcinomas (SC) of the lung are a heterogeneous group of nonsmall cell lung carcinomas (NSCLC) containing a sarcoma or sarcoma-like component. SC may represent an epithelial neoplasm undergoing divergent tissue differentiation originating from a single clone. Epithelial-mesenchymal transition (EMT) best describes the origin of the spindle and giant cells. We aimed to define chromosomal aberrations within the subgroups of SC and if EMT does play a role in SC. Twenty-two SC were investigated by chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 21 publications
3
48
0
2
Order By: Relevance
“…This assumption was further supported by the strong p53 protein accumulation in SCLC and spindle cell sarcoma, as well as the same amino acidic substitution (V274F) in exon 8 of TP53 gene in either tumor component. These findings are in keeping with the view that sarcomatous or sarcoma elements of pulmonary sarcomatoid carcinomas derive from carcinoma elements according to a process of sarcomatous metaplasia (conversion paradigm) during tumor progression rather than to be collision tumors [27][28][29]. In our case, the complete lack of epithelial differentiation in the spindle cell sarcoma component, which only focally retained rhabdomyoblastic features, made us hypothesize an almost complete myofibroblastic/smooth muscle transdifferentiation of carcinomatous cells rather than early divergence of the same ancestor lesion.…”
Section: Discussionsupporting
confidence: 83%
“…This assumption was further supported by the strong p53 protein accumulation in SCLC and spindle cell sarcoma, as well as the same amino acidic substitution (V274F) in exon 8 of TP53 gene in either tumor component. These findings are in keeping with the view that sarcomatous or sarcoma elements of pulmonary sarcomatoid carcinomas derive from carcinoma elements according to a process of sarcomatous metaplasia (conversion paradigm) during tumor progression rather than to be collision tumors [27][28][29]. In our case, the complete lack of epithelial differentiation in the spindle cell sarcoma component, which only focally retained rhabdomyoblastic features, made us hypothesize an almost complete myofibroblastic/smooth muscle transdifferentiation of carcinomatous cells rather than early divergence of the same ancestor lesion.…”
Section: Discussionsupporting
confidence: 83%
“…Schipf et al (2008) and Fles et al (2010) also reported genomic amplification of 19q in CS and CS cell lines have clonal abnormalities at 19q (Gorai et al, 1997). In addition, sarcomatoid carcinomas of the lung, which account for $ 1% of all lung tumors and have a worse prognosis than non-small cell lung cancer, frequently have chromosomal gains at 19q (Blaukovitsch et al, 2006). In this study, we analyzed genetic alterations of this locus in CS in detail by CGH microarray and identified amplification of 19p13, 19p12, and 19q13.…”
Section: Expression Profile Of Carcinosarcomamentioning
confidence: 88%
“…Except for the report from the Armed Forces Institute of Pathology by Fishback et al 2 They reported that tumor size > 5 cm, a clinical Stage > Stage I, and lymph node involvement shortened patient survival, significantly. The median survival of patients with sarcomatoid carcinoma was 10 months, which, when compared with that of ordinary lung carcinomas in the literature (20 months for adenocarcinoma, 18.5 months for squamous cell carcinoma, and 12.6 months for large cell carcinoma), was brief.…”
Section: Discussionmentioning
confidence: 96%